Association of Complement C3 with Clinical Deterioration Among Hospitalized Patients with COVID-19 - Jiang H; Chen Q; Zheng S; Guo C; Luo J; Wang H; Zheng X; Weng Z (International Journal of General Medicine, 2022)
Hongbo Jiang,1,* Qiaosen Chen,1,* Shaoping Zheng,2 Chunxia Guo,3 Jinzhuo Luo,3 Hua Wang,3 Xin Zheng,3 Zhihong Weng3 1Department of Epidemiology and Biostatistics, School of Public Health, Guangdong Pharmaceutical University, Guangzhou, People’s Republic of China; 2Department of Ultrasound, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Infectious Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhihong WengDepartment of Infectious Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 JieFang Avenue, Wuhan, 430022, People’s Republic of China, Email wengzh@hust.edu.cnBackground: The role of the complement system in coronavirus disease 2019 (COVID-19) remains controversial. This study aimed to evaluate the relationship between serum complement C3 levels, clinical worsening, and risk of death in hospitalized patients with COVID-19.Methods: Data were collected from 216 adults with COVID-19 admitted to a designated clinical center in Wuhan Union Hospital (China) between February 13, 2020, and February 29, 2020. Their complement C3 levels were measured within 24 h of admission. The primary outcome was a clinical worsening of 2 points on a 6-point ordinal scale. The secondary outcome was all-causes of death. Inverse probability of treatment weighting (IPTW) analysis was conducted to adjust for the baseline confounders.Results: The median value of C3 was 0.89 (interquartile range, 0.78– 1.01) g/L. Clinical worsening occurred in 12.3% (7/57) and 2.5% (4/159) of patients with baseline C3 levels < and ≥ 0.79 g/L, respectively (hazard ratio [HR], 5.22; 95% confidence interval [CI], 1.53– 17.86). After IPTW adjustment, the risk for clinical worsening was 4-fold greater (weighted HR, 4.61; 95% CI, 1.16– 18.4) in patients with C3 levels less than 0.79 g/L comparatively. The sensitivity analyses revealed the robustness of the results. No significant associations between C3 levels and death were observed on unadjusted (HR, 2.92; 95% CI, 0.73– 11.69) and IPTW analyses (weighted HR, 3.78; 95% CI, 0.84– 17.04).Conclusion: Low complement C3 levels are associated with a higher risk for clinical worsening among inpatients with COVID-19. The serum C3 levels may contribute to the identification of patient populations that could benefit from therapeutic complement inhibition.Keywords: SARS-CoV-2, COVID-19, complement C3, clinical worsening